Spectroscopic and astrometric radial velocities: hyades as a benchmark - Leão, Izan de Castro; Ludwig, Hans-Günter (Arxiv, 2018)
We study the accuracy of spectroscopic RVs by comparing spectroscopic and astrometric RVs for stars of the Hyades open cluster. Rather accurate astrometric RVs are available for the Hyades' stars, based on Hipparcos and on the first Gaia data release. We obtained HARPS spectra for a large sample of Hyades stars, and homogeneously analysed them. After cleaning the sample from binaries, RV variables, and outliers, 71 stars remained. The distribution of the observed RV difference (spectroscopic -- astrometric) is skewed and depends on the star right ascension. This is consistent with the Hyades cluster rotating at 42.3 +/- 10 m/s/pc. The two Hyades giants in the sample show, as predicted by gravitational redshift (GR), a spectroscopic RV that is blue-shifted with respect to the dwarfs, and the empirical GR slope is of 626 +/- 131 m/s, in agreement with the theoretical prediction. The difference between spectroscopic and astrometric RVs is very close to zero, within the uncertainties. In particular, the mean difference is of -33 m/s and the median is of -16 m/s when considering the Gaia-based RVs (corrected for cluster rotation), with a sigma of 347 m/s, very close to the expected cluster velocity dispersion. We also determine a new value of the cluster centroid spectroscopic RV: 39.36 +/- 0.26 km/s. The spectroscopic RV measurements are expected, from simulations, to depend on stellar rotation, but our data do not confirm these predictions. We finally discuss other phenomena that can influence the RV difference, such as cluster expansion, stellar activity, general relativity, and Galactic potential. Clusters within the reach of current telescopes are expected to show differences of several hundreds m/s, depending on their position in the Galaxy.
Gesehen am 05.11.2020